Heterogeneous trajectories of perceived stress and their associations with active leisure: a longitudinal study during the first year of COVID-19 - Karel Kulbin; Anna-Liisa Jõgi; Anna-Liisa Jõgi; Aleksander Pulver; Kristjan Kask (Frontiers Media S.A., 2024)
IntroductionThere is a plethora of literature on the dynamics of mental health indicators throughout the COVID-19 pandemic, yet research is scarce on the potential heterogeneity in the development of perceived stress. Furthermore, there is a paucity of longitudinal research on whether active leisure engagement, which typically is beneficial in reducing stress, might have similar benefits during times of major disruption. Here we aimed to extend previous work by exploring the dynamics of change in stress and coping, and the associations with active leisure engagement over the first year of COVID-19.MethodsData from 439 adults (Mage = 45, SD = 13) in Estonia who participated in a longitudinal online study were analyzed. The participants were assessed at three timepoints: April-May 2020; November-December 2020; and April-May 2021.ResultsMean stress and coping levels were stable over time. However, latent profile analysis identified four distinct trajectories of change in stress and coping, involving resilient, stressed, recovering, and deteriorating trends. Participants belonging to the positively developing stress trajectories reported higher active leisure engagement than those belonging to the negatively developing stress trajectories.DiscussionThese findings highlight the importance of adopting person-centered approaches to understand the diverse experiences of stress, as well as suggest the promotion of active leisure as a potentially beneficial coping resource, in future crises.